Human resource management in a business context - Price, Alan. (London : International Thomson Business Press, 1997)
Introduction to HRM. HRM and the business environment. The employment market. Organizational HRM. Culture and commitment. Strategic HRM. Resources: plans and strategies. Recruitment and selection. Managing diversity. Performance management. Developing people. Employee relations.
Keywords: Personnel management; Personnel management; Industrial management